Women experience the same ergogenic response to caffeine as men - Skinner, T. L.; Desbrow, B.; Arapova, J.; Schaumberg, M. A.; Osborbne, J.; Grant, G. D. (Medicine & Science in Sports & Exercise, 2019)
Purpose: This study aimed to determine whether 1) consumption of caffeine improves endurance cycling performance in women and 2) sex differences exist in the magnitude of the ergogenic and plasma responses to caffeine supplementation. Methods: Twenty-seven (11 women and 16 men) endurance-trained cyclists and triathletes participated in this randomized, double-blind, placebo-controlled, crossover study. Participants completed an incremental exercise test to exhaustion, two familiarization trials, and two performance trials. Ninety minutes before the performance trials, participants ingested opaque capsules containing either 3 mg·kg-1 body mass of anhydrous caffeine or a placebo. They then completed a set amount of work (75% of peak sustainable power output) in the fastest possible time. Plasma was sampled at baseline, preexercise, and postexercise for caffeine. Strict standardization and verification of diet, hydration, training volume and intensity, and contraceptive hormone phase (for women) were implemented. Results: Performance time was significantly improved after caffeine administration in women (placebo: 3863 ± 419 s, caffeine: 3757 ± 312 s; P = 0.03) and men (placebo: 3903 ± 341 s, caffeine: 3734 ± 287 s; P < 0.001). The magnitude of performance improvement was similar for women (mean = 4.3%, 95% CI = 0.4%-8.2%) and men (4.6%, 2.3%-6.8%). Plasma caffeine concentrations were similar between sexes before exercise, but significantly greater in women after exercise (P < 0.001). Conclusions: Ingestion of 3 mg/kg body mass of caffeine enhanced endurance exercise performance in women. The magnitude of the performance enhancement observed in women was similar to that of men, despite significantly greater plasma caffeine concentrations after exercise in women. These results suggest that the current recommendations for caffeine intake (i.e., 3-6 mg/kg caffeine before exercise to enhance endurance performance), which are derived almost exclusively from studies on men, may also be applicable to women